E-026 Predictive Factors of Outcome and Haemorrhage After Acute Ischaemic Stroke Treated by Mechanical Thrombectomy. (14th July 2013) - Pierot, L; Soize, S; Barbe, C; HKadziolka, K; Estrade, L; Serre, I
Abstract : Purpose: The study attempts to identify notable factors predicting poor outcome, death and intracranial-haemorrhage in patients with acute ischaemic stroke undergoing mechanical thrombectomy with stent-retriever. This data could be useful to improve the selection of patients for thrombectomy. Material and Methods: Patients with acute ischaemic stroke treated with the Solitaire FR device were retrospectively analysed from a prospectively collected database. We assessed the effect of selected demographic characteristics, clinical and imaging factors on poor outcome at 3 months (modified Rankin score 3–6), mortality at 3 months and haemorrhage at day 1 (symptomatic and asymptomatic). Results: From May 2010 to April 2012, 59 consecutive patients with an acute ischaemic stroke underwent mechanical thrombectomy. At 3 months, 57.6% of the patients were functionally independent (mRS 0–2) and mortality was 20.4%. Multivariate analyses revealed that a thrombus length>14mm (p=0.02; OR 7.55; CI 95% 1.35-42.31) and longer endovascular procedure duration (p=0.01; OR 1.04; CI 95% 1.01-1.07) were independently associated with poor outcome. A higher baseline ASPECT score (p=0.04; OR 0.79 per point; CI 95% 0.63-0.99) and successful recanalisation (p=0.02; OR 0.07; CI 95% 0.01-0.72) were independent predictors of good functional outcome. Baseline ASPECT score (p<0.01; OR 0.65; CI 95% 0.54-0.78) independently predicted symptomatic intracranial haemorrhage at day1. Conclusion: A thrombus length >14mm is an independent predictor of poor functional outcome at 3 months after thrombectomy. Absolute baseline ASPECT score reflects early symptomatic haemorrhage risk and functional outcome at 3 months. Further analyses are needed to determine the importance of the thrombus length in the selection of patients for mechanical thrombectomy. Disclosures: L. Pierot: 2; C; Covidien/EV3. S. Soize: None. C. Barbe: None. K. HKadziolka: None. L. Estrade: None. I. Serre: None.